PERTANGGUNGJAWABAN PIDANA TERHADAP PROMOSI JUDI ONLINE YANG DILAKUKAN OLEH ARTIS BERDASARKAN UNDANG-UNDANG NOMOR 1 TAHUN 2024 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Fedriansyah, Alvin; Fathurokhman, Ferry; Rofiana, Reine (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2025)
The development of information technology has encouraged the emergence of a new phenomenon in the world of gambling, namely online gambling, which is now promoted massively through social media, including by artists or public figures. The practice of promoting online gambling by artists not only causes social unrest but also becomes a challenge in law enforcement in Indonesia. The case of Wulan Guritno and several other artists who are suspected of promoting online gambling sites is a real example of the weak law enforcement against such violations. This study identifies two main problems, namely what form of criminal responsibility is given to online gambling promotions carried out by artists, and what efforts are made by law enforcement officers to deal with the phenomenon of online gambling promotions on Instagram. This study uses the theory of criminal responsibility and the theory of overcoming criminal acts as the basis for analysis. The method used in this study is the normative legal method combined with field research through interviews with law enforcement officers. Data was obtained from primary, secondary, and tertiary legal materials and supported by literature studies and interviews with the parties concerned. The results of this study are that artists who promote online gambling can be held criminally responsible because they have fulfilled the criminal elements in Article 27 paragraph (2) in conjunction with. Article 45 paragraph (3) of Law Number 1 of 2024 concerning Electronic Information and Transactions. However, law enforcement is still not optimal. Therefore, strict sanctions are needed as well as strengthening of regulations and digital education to suppress the promotion of online gambling, especially through social media. And regarding, efforts to overcome this by law enforcement officers have taken several steps, including digital monitoring, legal action against perpetrators of promotion, and outreach to the public. However, prevention still faces various obstacles such as limited resources, many anonymous accounts. Therefore, strict sanctions are needed as well as strengthening of regulations and digital education to suppress the promotion of online gambling, especially through social media.